Development of read-one-write-all synchronization transaction daemon (row A-STD) in distributed system - Ahmad, Noraziah; Mohd Sidek, Roslina; Ramli, Muhammed Ramiza; Junaida, Sulaiman; Jamil, Norazaliza Mohd; Hamid, Roslina Abdul; Noor, Noorhuzaimi Karimah (2010)
In the world where internet does all the business nowadays, the demand of transmitted information over networks increase rapidly and the demand for steady bandwidth seems to be out of control. Particularly organizations need to provide updated data to users that might be geographically remote and handling a vast amount of requested data distributed in multiple sites. In distributed system environment, replicated data is the current trend to keep data updated in multiple sites. Replication in distributed environment has become increasingly popular due to its high degree of availability, fault tolerance and enhance the performance of a system. These advantages of replication are important because it enables organizations to provide users with access to current data anytime or anywhere even if the users are geographically remote. At certain time, access to the current data can be made anywhere in distributed systems. However, this way of data organization also introduces low data consistency among replicas when changes are made during transactions. The need to have a system to monitor this data replication arises. Read-One-Write-All Monitoring Synchronization Transaction System (ROW A-MSTS) is developed to answer the issue of problem made by the ROW A replication technique. A new algorithm has been designed and developed to manage replication and transaction using ROW A-MSTS prototype. The proposed algorithm through ROWA-MSTS prototype was experiment in distributed systems environment. Rapid Application Development (RAD) is the software life cycle used to develop this project due to short period of development time. By using ROW AMSTS, it helps to monitor the replicated data distribution over multiple sites while maintaining the data consistency.